Pharmacokinetic profile of PBRM in rodents, a first selective covalent inhibitor of 17β-HSD1 for breast cancer and endometriosis treatments. Issue 178 (April 2018) - Maltais, René; Trottier, Alexandre; Roy, Jenny; Ayan, Diana; Bertrand, Nicolas; Poirier, Donald
Graphical abstract: Highlights: Pharmacokinetics of PBRM, a potent 17β-HSD1 inhibitor, have been addressed in rodents. High doses of PBRM are very well tolerated by mice for a period of several weeks. Distribution of 3 H-PBRM shows a wide distribution among different mouse organs. Metabolism studies of PBRM have identified PBRM-O as the sole metabolite. The steroid derivative PBRM shows a good excretion profile and bioavailability. Abstract: The development of a covalent inhibitor of 17β-hydroxysteroid dehydrogenase type 1 (17β-HSD1) is a promising approach for the treatment of hormone-dependent breast cancer and endometriosis. After reporting the steroid derivative PBRM as a first potent covalent inhibitor of 17β-HSD1 without estrogenic activity, we are now interested in studying its pharmaceutical behavior. The metabolism study in a human liver microsomal preparation showed a gradual transformation of PBRM into PBRM-O, an oxidized ketonic form of PBRM at position C17. Interestingly, PBRM-O also inhibits 17β-HSD1 and is not estrogenic in estrogen-sensitive T-47D cells. However, when PBRM was injected subcutaneously ( sc ) in mice, a very small proportion of PBRM-O was measured in a 24 h-time course experiment. A pharmacokinetic study in mice revealed suitable values for half-life (T1/2  = 3.4 h), clearance (CL = 2088 mL/h kg), distribution volume (Vz = 10.3 L/kg) and absolute bioavailability (F = 65%) when PBRM was injected sc at 14.7 mg/kg. A good F value of 33% was also obtained when PBRM was given orally. A tritiated version of PBRM, 3 H-PBRM, was synthesized and used for an in vivo biodistribution study that showed its gradual accumulation in various mouse tissues (peak at 6 h) followed by elimination until complete disappearance after 72 h. Elimination was found to occur in feces (93%) and urine (7%) as revealed by a mass balance experiment. PBRM was also evaluated for its toxicity in mice and it was found to be very well tolerated after weekly sc administration (30–405 mg/kg for 8 weeks) or by po administration (300–900 mg/kg for 4 weeks). Overall, these experiments represent important steps in the preclinical characterization of the pharmaceutical behavior of PBRM, as well as for its translation to clinical trials.